THE COUNSELLING TEACHERS’ ROLE ON THE IMPACT OF THE COVID-19 PANDEMIC WITH ONLINE LEARNING AT LAMPUNG BUDDHIST SUNDAY SCHOOL - Iketut Damana (Sean Institute, 2022)
The current situation in the world of education is increasingly unsatisfactory that requires counselling teachers to seek new strategies. The problem of counselling teacher is increasingly a useful option when online learning is properly studied. The purpose of counselling teachers in Sunday schools is to include the types of rules from the impact of the Covid-19 pandemic. As an online learning with a qualitative approach. Informants consist of 6 teachers. Research instrument by interview. One of the stages of the counselling role that is interesting from many researchers to produce Miles and Huberman's technique is the role of the counselling teacher. The finding of the importance of counselling teachers can be identified by three benchmarks; counselling teacher factors have an impact on students’ learning, student forms of online learning have an impact on counselling teachers, counselling teacher challenges have an impact on students' online learning